Symptom reduction in palliative care from single session mindful breathing : a randomised controlled trial - Mei, Ling Look; Seng, Beng Tan; Li, Li Hong; Chong, Guan Ng; Hway, Ann Yee; Liang, Yik Lim; Ng, Diana Leh-Ching; Chee, Shee Chai; Ee, Chin Loh; Chee, Loong Lam (BMJ Publishing Group Ltd., 2020)
Context There has been increasing evidence of the role of mindfulness-based interventions in improving various health conditions. However, the evidence for the use of mindfulness in the palliative care setting is still lacking. Objectives The objective of our study was to determine the efficacy of a single session of 20 min mindful breathing in alleviating multiple symptoms in palliative care. Methods Adult palliative care in patients with at least one symptom scoring ≥5/10 based on the Edmonton Symptom Assessment Scale (ESAS) were recruited from September 2018 to December 2018. Recruited patients were randomly assigned to either 20 min mindful breathing and standard care or standard care alone. Results Forty patients were randomly assigned to standard care plus a 20 min mindful breathing session (n=20) or standard care alone (n=20). There was statistically significant reduction of total ESAS score in the mindful breathing group compared with the control group at minute 20 (U=98, n 1 = n 2 = 20, mean rank 1 = 15.4, mean rank 2 = 25.6, median reduction 1 = 6.5, median reduction 2 = 1.5, z=−2.763, r=0.3, p=0.005). Conclusion Our results provided evidence that a single session of 20 min mindful breathing was effective in reducing multiple symptoms rapidly for palliative care patients.